Hi! I don�t understand this question: 10. Select the equivalent answer for the code given below? boolean b = true; if ( b ) { x = y; } else { x = z; } A) x = b ? x = y : x = z ; B) x = b ? y : z ; C) b = x ? y : z ; D) b = x ? x = y : x = z ; The answer is B but why x = b??? I think that the correct answer will be (x == true) ? y : z; Thank you in advance.

Hi jordi, The ternary operator x=(a?b:c) allows to replace an if-else statement of this form: if(a) x=b else x=c Thus, a has to be a boolean expression. B is the correct answer because b is a boolean expression and x gets assigned y if b is true and z otherwise. In this example b is true since it is declared and initialized as such at the top of the code... Hope that helps Val

Hi Jordi, x = b ? y : z ; consider only this: b ? y : z means if b is true - y else - z now x = b ? y : z ; means if b is true - x=y else - x=z I think i have not made it very clear. Ask if u still have doubt.